Conceptions on disability of Spanish university students - Leite, Lucia Pereira [UNESP]; Martins, Sandra [UNESP]; Morina, Anabel; Morgado, Beatriz (Univ Politecnica Salesiana Ecuador-salesian Polytecnic Univ, 2023)
In the context of education and, specifically, in the university stage, the presence of people with disabilities in Higher Education is today a reality, both in Spain and in other international contexts. Currently, there is a global movement that claims the right to access, permanence and success of non-traditional students, including those with disabilities. This study aims to present and analyze the conceptions of 676 university students (undergraduate and postgraduate) from different areas of knowledge of the University of Seville (Spain) on disability. A quantitative methodology has been used with the application of the Intercultural Scale of Disability Concepts (EICD). The results showed a preponderance of the social conception of disability, followed by the biological/medical aspects. Differences were observed in relation to the variables analyzed, younger university students and those who were doing postgraduate studies indicated the prevalence of statements linked to the social model of disability. No significant differences were found between participants with and without disabilities. Among the conclusions, we can highlight the relevance of understanding disability as a social phenomenon for the offer of inclusive psychosocial and psychoeducational practices. This decision then reveals that accepting the review of social paradigms to resignify concepts in the social conception of disability is a possible for the recognition of the differences that constitute the human.
Keywords: University students; disability; concept formation; evaluation measures; public policy; social psychology